Analysis of Individual Characteristics and Use of Media in The Adoption Process of Social Media Innovation for Tourist Village Management - Notonegoro, Muhammad Ridho; Purnaningsih, Ninuk; Matindas, Krishnarini (Jurnal Locus Penelitian dan Pengabdian, 2025)
The tourism sector can function as a catalyst for development (agent of development). Kampung Blekok is one of the tourist villages included in the 20 Tourist Attractions of Situbondo Regency that managed to survive during the pandemic where Kampung Blekok won 1st place for the best pioneering village in the 2021 Tourism Village Award (ADWI). In an effort to restore the tourism sector, the promotional aspect plays an important role in attracting visitors. The development of communication technology is very rapid where currently information is widely available digitally. Instagram and Tiktok are the types of social media sharing networks that are most widely used in Indonesia. Instagram and Tiktok continue to create innovations in their photo and video editing features. Kampung Blekok itself has used social media sharing networks such as Instagram and Tiktok as promotional media. The role of creative and innovative content is the main spearhead in attracting tourists. For this reason, tourism village managers must continue to follow the development of innovations in the features developed by Instagram and Tiktok platform developers in order to create promotional content that is up to date and attracts the attention of potential visitors. This study aims to analyze (1) individual characteristics, media use, and environmental support in the process of adopting innovation in the use of Instagram and TikTok features by the managers of the Kampung Blekok tourist village; (2) stages of adoption of innovation in the use of Instagram and TikTok features by the managers of the Kampung Blekok tourist village; (3) factors that influence the adoption of innovation in the use of Instagram and TikTok features on the stages of innovation adoption gone through by the managers of the Kampung Blekok tourist village. The population and sample were determined by the census method with a total of 50 respondents from Kampung Blekok managers. Data processing and analysis were carried out using descriptive statistics and inferential statistical tests using SmartPLS software.